Transport economics - Button, Kenneth 1948- (Edward Elgar, 2010)
Applies economic analysis to transport issues. This work examines in general terms the many aspects of the demand for, and supply of, transport together with the various methods of government intervention needed to ensure that social and environmental criteria are attained.